Turkish validity and reliability of the Diabetes Self-Efficacy Scale - Mankan, Talip; Erci, Behice; Turan, Gulcan Bahcecioglu; Akturk, Ummuhan (Elsevier, 2017)
Purpose: The aim of this methodological study was to determine the validity and reliability of the Diabetes Self-Efficacy Scale adapted to the Turkish community. Methods: The study sample was completed with 319 patients who had been diagnosed at least 1 year before and hospitalized in the Malatya Turgut Ozal Health Center and Malatya State Hospital in Turkey. A questionnaire that consists of items on sociodemographic characteristics, drug use and information about the disease of patients and the Diabetes Self-Efficacy Scale were used for data collection in the study. In reliability analysis of the scale, the Cronbach's alpha coefficient was calculated and item analysis method was utilized. Factor analysis was used for the construct validity, and Principal Component Analysis and Varimax Rotation method were used for analyzing the factor structures. Results: According to data obtained in the study, item-total correlation of the items of the scale was found to be at an adequate level (0.297-0.803). The scale's Cronbach's alpha reliability coefficient was found to be 0.86, and there was one factor that explains 52.38% of the total variance with an eigenvalue was greater than 1.0. As a result of the analysis, the factor loadings of the items of the scale were found to be between 0.59 and 0.81. Conclusion: Diabetes Self-Efficacy Scale is a valid and reliable instrument for determining the self-efficacy of patients and providing a proper care. It can be suggested to investigate and evaluate the consistency of the scale by applying it to broader sample groups representing different socioeconomic levels. (C) 2017 Chinese Nursing Association. Production and hosting by Elsevier B.V.
Keywords: Diabetes mellitus; Diabetes Self-Efficacy Scale; Nursing; Reliability; Self-efficacy; Validity